2018
DOI: 10.14303/er.2017.217
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of student’s perception towards group work – a Middle East perspective

Abstract: Group works have become an integral component of modern education system. The focus of this study is to explore the students' perception of group works. Based on a pilot study with 64 students and subsequent study with 274 participants, this research provides a holistic reading on group works from students' perspectives. The study analyses relative preference of students between individual and group assignments, advantages and disadvantages of group works and the strategies followed by the students in the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is not only an inequitable exchange but also a threat to delivery of quality education and its ultimate goal of producing quality teachers. This kind of unfairness is even multiplied when there is no proper mechanisms of awarding marks on the basis of individual contribution to group work as previously reported (Hall & Buzwell, 2012;Hassanien, 2006;Refeque, Balakrishnan, Inan & Harji, 2018). This, indeed, needs to be rethought if the value of using group work has to be attained in higher education, particularly when preparing teachers for the 21st Century teaching and learning (Geisinger, 2016;Kereluik, Mishra, Fahnoe & Terry, 2013;Mishra & Mehta, 2017).…”
Section: Reactions To Social Loafersmentioning
confidence: 95%
“…This is not only an inequitable exchange but also a threat to delivery of quality education and its ultimate goal of producing quality teachers. This kind of unfairness is even multiplied when there is no proper mechanisms of awarding marks on the basis of individual contribution to group work as previously reported (Hall & Buzwell, 2012;Hassanien, 2006;Refeque, Balakrishnan, Inan & Harji, 2018). This, indeed, needs to be rethought if the value of using group work has to be attained in higher education, particularly when preparing teachers for the 21st Century teaching and learning (Geisinger, 2016;Kereluik, Mishra, Fahnoe & Terry, 2013;Mishra & Mehta, 2017).…”
Section: Reactions To Social Loafersmentioning
confidence: 95%
“…Perhaps the most frequent and consistent frustration expressed by students is their concern about free-riding (Albanese & Van Fleet, 1985) or social loafing expected from other students and allowed, accepted, or implicitly disregarded by educators (Ashraf, 2004;Boren & Morales, 2018;Burdett, 2003;Jassawalla et al, 2009;McCorkle et al, 1999;Pfaff & Huddleston, 2003;Saghafian & O'Neill, 2018;Taggar & Neubert, 2008). Freeriding is such a central issue for students participating in team work activities that similar concerns and frustrations have been unearthed in a variety of contexts all around the world (Clark & Baker, 2011;Mbalamula, 2018;Njie et al, 2013;Popov et al, 2012;Refeque et al, 2018).…”
Section: The Realities Of Team Work In Business Coursesmentioning
confidence: 99%
“…There have been many past studies on group work. A study conducted by Refeque et al (2018) on their research on the students' perception towards group work, had involved 274 participants to investigate their perceptions of completing the assignment individually or in a group. This study revealed that students with higher Cumulative Grade Point Average (CGPA) preferred to do the tasks individually.…”
Section: Past Studies On Group Workmentioning
confidence: 99%